Prevalence of Computer Vision Syndrome Among Engineering and Nursing College Students in Bangalore. - Sah, Sanjay Kumar; Chhetri, Prabin; Hegde, Namratha; Dahal, Manish (Optometry & Visual Performance, 2020)
Background: Computer vision syndrome (CVS) is a group of visual symptoms experienced during the use of computers. Globally, about 60 million people suffer from CVS, resulting in reduced productivity at work and decreased quality of life. The present study aims to determine the prevalence of CVS and create awareness about CVS among engineering and nursing college students in Bangalore, India. Methods: A prospective study was conducted among students of engineering and nursing colleges in Bangalore, India. Students in the age group of 17-35 years were included in the study. A brief history, along with details on hours of computer usage, was documented. Each subject underwent an optometric examination to investigate non-strabismic binocular vision dysfunctions and dry eye. Each subject completed a symptom survey. Results: A total of 247 students between the ages of 17 and 35 years from four different colleges in Bangalore were assessed. Of the 247 students, 108 students were from engineering college and 139 students were from nursing college. In addition, 25.12% were male and 74.89% were female. The overall prevalence of CVS was found to be 85.02%. The prevalence of CVS among engineering students and nursing students was 86.11% and 84.17%, respectively. Conclusion: The present study revealed a high prevalence of CVS among students; more than three-fourths of the students were symptomatic. These preliminary results indicate a need for improved awareness, diagnosis, and management of binocular dysfunctions to increase the academic potential of these students and to increase productivity.